PENGGUNAAN BEBERAPA MEDIUM SEMISINTETIK UNTUK PRODUKSI MISELIUM JAMUR MAITAKE (Grifola frondosa (Dickson: Fr.) S. F. Gray) ISOLAT CIANJUR DAN EKSTRAK KASARNYA - Maria Mardhitama Maharani; Nuniek Ina Ratnaningtyas; Slamet Priyanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Research on the use of some semisynthetic medium for the production of fungal mycelium Maitake (Grifola frondosa (dickson: Fr.) SF Gray) isolates Cianjur and crude extract was performed with an incubation period of 30 days. This study aimed to determine the ability of green bean, cowpea and maize as an alternative material of semisynthetic medium for manufacturing G. frondosa’s mycelium and and to know the production of G. frondosa’s mycelium and the highest crude extract. This study was experimental study with a completely randomized design consisted of 4 treatments : Yeast Potato Dextrose Broth (PDYB) medium, Green bean Yeast Dextrose Broth (GbDYB) medium, Cowpea Yeast Dextrose Broth (CpDYB) medium and Corn Yeast Dextrose Broth (CDYB) medium. The highest average dry weight of mycelium (1,584 g/100ml) was GbDYB medium. The lowest average dry weight of the mycelium (g/100ml 0.244) was PDYB medium. The weight of the crude extract of mycelium in each treatment was lower than the dry weight. The highest weight of the crude extract was obtained from the GbDYB medium treatment (1,22 g) and the lowest was obtained from PDYB medium (0,113 g). Anova test results of different treatment was very significant, meaning that the use of extract of green bean, cowpea and maize greatly affected the growth of G.frondosa’s mycelium. The LSD test between treatment of PDYB medium and CDYB medium was not significant, meaning that the increase of mycelium’s growth on PDYB medium had no different with the CDYB medium.